CD24 associates with EGFR and supports EGF/EGFR signaling via RhoA in gastric cancer cells. Issue 1 (December 2016) - Deng, Wenjie; Gu, Luo; Li, Xiaojie; Zheng, Jianchao; Zhang, Yujie; Duan, Biao; Cui, Jie; Dong, Jing; Du, Jun
Abstract Background CD24, a mucin-like membrane glycoprotein, plays a critical role in carcinogenesis, but its role in human gastric cancer and the underlying mechanism remains undefined. Methods The contents of CD24 and epidermal growth factor receptor (EGFR) in gastric cancer cells (SGC-7901 and BGC-823) and non-malignant gastric epithelial cells (GES-1) were evaluated by Western blotting assay. Cellular EGFR staining was examined by immunofluorescence assay. Cell migration rate was measured by wound healing assay. The effects of depletion/overexperssion of CD24 on EGFR expression and activation of EGF/EGFR singaling pathways were evaluated by immunofluorescence, qPCR, Western blotting and flow cytometry techniques. RhoA activity was assessed by pulldown assay. CD24 and EGFR expression patterns in human gastric tumor samples were also investigated by immunohistochemistry staining. Results CD24 was overexpressed in human gastric cancer cells. Ectopic expression of CD24 in gastric epithelial cells augmented the expression of EGFR, while knockdown of CD24 in gastric cancer cells decreased the level of EGFR and cell migration velocity. To further explore the mechanisms, we investigated the effect of CD24 expression on EGF/EGFR signaling. We noticed that this effect of CD24 on EGFR expression was dependent on promoting EGFR internalization and degradation. Lower ERK and Akt phosphorylations in response to EGF stimulation were observed in CD24-depleted cells. In addition, we noticed that the effect of CD24 on EGFR stability was mediated by RhoA activity in SGC-7901 gastric cancer cells. Analysis of gastric cancer specimens revealed a positive correlation between CD24 and EGFR levels and an association between CD24 expression and worse prognosis. Conclusion Thus, these findings suggest for the first time that CD24 regulates EGFR signaling by inhibiting EGFR internalization and degradation in a RhoA-dependent manner in gastric cancer cells.